IMPROVING TAX ADMINISTRATION - ITS ROLE IN SMALL BUSINESS AND PRIVATE ENTREPRENEURSHIP (INTERNATIONAL CONFERENCE ON ANALYSIS OF MATHEMATICS AND EXACT SCIENCES, 2024)
Tax administration plays a crucial role in the functioning of small businesses and private entrepreneurship. Efficient tax administration not only ensures compliance with legal requirements but also fosters a conducive environment for business growth and economic development. This article explores various strategies and approaches to improving tax administration and discusses their implications for small businesses and private entrepreneurship. By examining the challenges faced by both tax authorities and businesses, this article aims to provide insights into the importance of effective tax administration in promoting business sustainability and economic prosperity